Cutaneous Angiomyolipoma—a distinct entity that should be separated from classic Angiomyolipoma: complete review of existing cases and defining fundamental features - Sánchez, Natalia Gabriela; Ávila Romay, Alfonsina Angelica; Martínez Luna, Eduwiges; Padilla Rodríguez, Álvaro Lezid (My University, 2022)
Cutaneous angiomyolipoma is a rare mesenchymal tumor that is demographically, clinically, and immunohistochemically distinct from its renal and extrarenal counterparts. We present a case of cutaneous angiomyolipoma in the right retroauricular area of a 35-year-old male patient and provide a broad systematic review of the literature and the largest compilation of cutaneous angiomyolipomas reported to date. According to the findings presented in this review, we conclude that cutaneous angiomyolipoma should be completely separated from renal and extrarenal angiomyolipomas and therefore be considered a distinct entity in the classification of skin tumors. ©The authors, JMIR Dermatology